Pengaruh Profitabilitas, Solvabilitas, Opini Audit, Dan Umur Perusahaan Terhadap Audit Delay: Studi Pada Perusahaan Consumer Cyclical Tahun 2019-2021 - Lubna Lubna; Usdeldi Usdeldi; Khairiyani Khairiyani (Jurnal Publikasi Manajemen Informatika, 2023)
This study aims to determine the effect of Profitability, Solvability, Audit Opinion, and Company Age on Audit Delay in Consumer Cyclical companies registered with ISSI in 2019-2021. This study uses secondary data in the form of company annual reports that are the samples in the study and can be obtained from the Indonesia Stock Exchange's website. Samples were taken using a purposive sampling technique, totaling 21 companies. The data analysis technique used is descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing. Based on the results of the study, it shows that Profitability and Audit Opinion can partially have a significant effect on Audit Delay, while Solvency and Firm Age partially have no significant effect on Audit Delay. Then, simultaneously Profitability, Solvability, Audit Opinion, and Company Age can have a significant effect on Audit Delay. The amount of simultaneous influence is shown by the R square value of 19%.